Distribution and key influential factors of dissolved oxygen off the Changjiang River Estuary (CRE) and its adjacent waters in China. Issue 1 (15th December 2017) - Chi, Lianbao; Song, Xiuxian; Yuan, Yongquan; Wang, Wentao; Zhou, Peng; Fan, Xin; Cao, Xihua; Yu, Zhiming
Abstract: Based on two multidisciplinary investigations conducted in summer and winter 2015, the distribution of dissolved oxygen (DO) and the associated seasonal variations off the Changjiang River Estuary (CRE) were studied. The DO content was high in winter, ranging from 6.81–10.29 mg/L, and the distribution was mainly controlled by temperature and salinity. The DO concentration was 1.92–9.67 mg/L in summer, and a hypoxic zone (DO < 3 mg/L) covered 14, 800 km 2, which was mainly controlled by stratification and organic matter decomposition. The hypoxic zone exhibited a "dual-core" structure and the differences in the biochemical and physical processes between the southern and northern regions were compared: the northern region exhibited stronger pycnocline intensity; while larger biomass and higher TOC as well as TN contents were observed in the southern region. Hypoxia in the northern region might be mainly dominated by stratification, while that in the southern region was mainly associated with organic matter decomposition. Highlights: Hypoxia off the CRE exhibited a "dual-core" structure in summer. Hypoxia in the northern region might be mainly dominated by stratification. Organic matter decomposition contributed more to hypoxia in the southern region.